Analysis Effect of Personnel Competence in Medicine and Health (BIDDOKKES) on Health Service Satisfaction in Southeast Sulawesi Regional Police - Machmud, Sri Wulan; Binekada, I Made Christian; Yusran, Sartiah (PT. Riset Press International, 2024)
The aim of this research is to examine the influence of skills on the satisfaction of service personnel in the Medical and Health Affairs of the Southeast Sulawesi Regional Police Department. Analyzing the knowledge towards the satisfaction of service personnel in the Medical and Health Affairs of the Southeast Sulawesi Regional Police Department. Analyzing the social roles towards the satisfaction of service personnel in the Medical and Health Affairs of the Southeast Sulawesi Regional Police Department. Analyzing the self-image towards the satisfaction of service personnel in the Medical and Health Affairs of the Southeast Sulawesi Regional Police Department. Analyzing the attitudes towards the satisfaction of service personnel in the Medical and Health Affairs of the Southeast Sulawesi Regional Police Department. This research adopts a cross-sectional approach. The population in this study consists of 351 personnel. The results of this study indicate that skills significantly influence the satisfaction of service personnel in the Medical and Health Affairs of the Southeast Sulawesi Regional Police Department. Knowledge significantly influences the satisfaction of service personnel in the Medical and Health Affairs of the Southeast Sulawesi Regional Police Department. Social roles significantly influence the satisfaction of service personnel in the Medical and Health Affairs of the Southeast Sulawesi Regional Police Department. Self-image has no significant effect on service satisfaction for Medical and Health Personnel at the Southeast Sulawesi Regional Police. Attitudes significantly influence the satisfaction of service personnel in the Medical and Health Affairs of the Southeast Sulawesi Regional Police Department.